1998
DOI: 10.1038/sj.bmt.1701483
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian function after autologous bone marrow transplantation in childhood: high-dose busulfan is a major cause of ovarian failure

Abstract: Summary:We studied pubertal status and ovarian function in 21 girls aged 11-21 years who had earlier received 1.2-13 years (median 7 years) high-dose chemotherapy and autologous BMT without TBI for malignant tumors. Ten of them were given busulfan (600 mg/m 2 ) and melphalan (140 mg/m 2 ) with or without cyclophosphamide (3.6 g/m 2 ). Eleven others did not receive busulfan. Twelve girls (57%) had clinical and hormonal evidence of ovarian failure. Among nine others who had completed normal puberty, six had norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(102 citation statements)
references
References 26 publications
6
87
2
7
Order By: Relevance
“…In contrast, girls receiving similar intensive therapy followed by a non-BU-containing BMT therapy, are more likely to have normal gonadotrophins. 19,20 This has been seen particularly with single agent melphalan. 20 Although the majority of children undergoing BMT for AML are conditioned with BUCY, good results have been reported with the use of melphalan alone.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, girls receiving similar intensive therapy followed by a non-BU-containing BMT therapy, are more likely to have normal gonadotrophins. 19,20 This has been seen particularly with single agent melphalan. 20 Although the majority of children undergoing BMT for AML are conditioned with BUCY, good results have been reported with the use of melphalan alone.…”
Section: Discussionmentioning
confidence: 95%
“…19,20 This has been seen particularly with single agent melphalan. 20 Although the majority of children undergoing BMT for AML are conditioned with BUCY, good results have been reported with the use of melphalan alone. 21 If these results could be duplicated in a larger group of patients, preferably in a randomised study comparing BUCY with melphalan, then it would be reasonable to prefer the less toxic conditioning regimen.…”
Section: Discussionmentioning
confidence: 95%
“…This stems from the observation that the incidence of immediate amenorrhea is lower in younger women. Because young women have a larger primordial follicle pool, they are less likely to lose all their reserve immediately, but because they have lost a significant proportion of it, they will eventually experience premature ovarian failure [34][35][36][37][38]. On the other hand, permanent gonadal damage can be induced with smaller doses of the implicated chemotherapeutic agents in older women with lower primordial follicle reserve.…”
Section: The Impact Of Chemotherapeutic Agents On Ovarian Functionmentioning
confidence: 99%
“…35 We found that hypogonadism was significantly associated with conditioning with TBI or TAI, but not with the type of conditioning chemotherapy, perhaps owing to the high percentage of patients who received alkylating agents. Older age and advanced pubertal stage at BMT were both significantly associated with hypogonadism, although Teinturier et al 36 found that high-dose busulfan is a major cause of ovarian failure, even when given in the prepubertal period without TBI or abdominal or pelvic radiotherapy.…”
Section: Thyroid Dysfunctionmentioning
confidence: 99%